The Influence of Brand Image on Consumer Purchase Decisions for Class Mild. Cigarettes - Adi Surya Wiranegara (TRIGIN PUBLISHER, 2020)
This study aims to determine the effect simultaneously and partially between the variable brand image and purchasing decisions, as well as the dominant variables influencing consumer purchasing decisions for Clas Mild Cigarettes. This research is included in the type of exsplanatory research, where this research is designed to explain the causal relationship that occurs between the brand image variables of the Clas Mild brand cigarettes which consist of the image of the maker (X1), user image (X 2), product image (X 3) with consumer purchasing decisions (Y). To determine the number of respondents, the researcher used Sri Rahayu's opinion, with a sample of 80 respondents. While the sampling technique used purposive sampling. The data analysis technique used is multiple regression, F test, and t test. From the results of t-test, F-test and multiple regression, it can be seen that the three variables, namely the image of the maker/corporate image (X1), the image of the user/user image (X2), and the image of the product/product image (X3) have a significant influence on purchasing decisions. Class Mild cigarettes. From the results of the analysis, it is known that the product image variable (X1) is the dominant variable influencing purchasing decisions. Based on this research, it can be seen that the contribution of the brand image variable to purchasing decisions is 61.4%, while the remaining 38.6%.